2009
DOI: 10.1111/j.1468-2311.2008.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Practice in Mental Health Diversion and Liaison

Abstract: Many criminal justice mental health diversion and liaison teams are under threat of extinction. Nacro (2005) notes a steady decline in their number, despite the fact that these schemes in principle provide a valuable service and can fit any social inclusion or crime preventative agenda. In order for such teams and schemes to thrive they need to be strengthened urgently, a point concurred with by Jack Straw when he asked Lord Bradley to undertake a review into mental health diversion as a means of reducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…To assess to what extent these areas of practice are carried out in a sustainable and cost effective way, we test the absence or presence of six criteria of effective practice. These are Statement of Purpose, Policy, Management, Resourcing, Practice, and Continuous Professional Development (for further debate on these see Pakes and Winstone, 2008a). The evidence suggests that such elements are fundamental to the sustainable success of schemes (Winstone and Pakes, 2009).…”
Section: The Mental Health Effective Practice Audit Checklist (Mhep-amentioning
confidence: 97%
See 1 more Smart Citation
“…To assess to what extent these areas of practice are carried out in a sustainable and cost effective way, we test the absence or presence of six criteria of effective practice. These are Statement of Purpose, Policy, Management, Resourcing, Practice, and Continuous Professional Development (for further debate on these see Pakes and Winstone, 2008a). The evidence suggests that such elements are fundamental to the sustainable success of schemes (Winstone and Pakes, 2009).…”
Section: The Mental Health Effective Practice Audit Checklist (Mhep-amentioning
confidence: 97%
“…That said we have argued elsewhere (Pakes and Winstone, 2008a) that these schemes have seen almost two decades of decline with their number dwindling and their work frequently unrecognised. The NACRO survey that was carried out in 2004 demonstrated this (NACRO, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Lack of government guidelines, competing professional interests and tensions inherent in multi-agency working led to national differences in the development of CJLDS models (National Association for the Care and Resettlement of Offenders, 2004; Brooker and Ullman, 2009; Pakes and Winston, 2009; James, 2010), including: single practitioners versus multi-agency schemes; part-time or on-call services compared with full-time dedicated teams; panel assessment schemes compared with front-line proactive teams; reactive compared with proactive screening; and variations in the services offered by a CJLDS which might include some or all of the following: mental health assessment in police stations, reports to court, providing recommendations on sentence and management, managing and sharing information with probation and prisons, short-term treatment and access to inpatient beds.…”
Section: Challenges For the First Wavementioning
confidence: 99%
“…The results demonstrated that L&D efforts had a substantial impact on decreasing the number of arrests (Bonkiewicz et al, 2014) and increasing positive outcomes for primary health care (Earl et al, 2015). However, organisational aspects behind L&D's influence were underexplored (Pakes & Winstone, 2009. This book chapter addresses this shortfall by grappling with L&D's organisational processes and work activity.…”
Section: Introductionmentioning
confidence: 99%